Comparison of monocytic cell lines U937 and THP-1 as macrophage models for in vitro studies - Nascimento, Camyla Rodrigues [UNESP]; Rodrigues Fernandes, Natalie Ap [UNESP]; Gonzalez Maldonado, Laura Andrea [UNESP]; Rossa Junior, Carlos [UNESP] (Elsevier, 2022)
Understanding macrophage biology can improve comprehension of diverse biological processes and provide insights into novel therapeutic immunomodulatory strategies. Due to limited yield and technical difficulty in isolating primary macrophages, in vitro studies commonly use monocytes as precursor cells. Monocytic cell lines are a virtually unlimited source of macrophage precursors and two of the most frequently used cell lines are THP-1 and U937. Besides a great variability in macrophage differentiation protocols there is scarce information on possible differences in the biological responses of these cell lines. In this study, we used a standardized differentiation protocol using PMA and compared the response of macrophages derived from THP-1 and U937 cells to M1-and M2-polarizing conditions. THP-1-derived macrophages are more responsive to M1 stimuli and skewed towards M1 phenotype, whereas U937-derived macrophages were more responsive to M2 stimuli and skewed towards M2 phenotype. THP-1-derived macrophages also had greater production of ROS and phagocytic activity. Under M1-polarizing conditions, macrophages derived from both THP-1 and U937 reduced phagocytosis activity and the increased production of ROS. This information should be considered to make an informed choice on the cell line used as in vitro macrophage model, according to the experimental goals and biological context.
Keywords: Gene expression; Macrophage; Phenotype; THP-1 cells; U937 cells